Does the current New Zealand case definition of serious non-fatal injury miss a material number of serious injury cases?. (1st March 2011) - Cryer, C; Gulliver, P; Langley, J; Davie, G; Samaranayaka, A
Abstract : Background: Similar to other countries, in New Zealand (NZ) a case of non-fatal injury is captured if the principal diagnosis (PDx) on the hospital discharge record is coded to the injury chapter of International Classification of Diseases (ICD). There has been recent debate in NZ about whether this operational definition captures all cases that are of interest to injury prevention practitioners and policy makers. Research question: Does the case definition of serious non-fatal injury, used in the specifications of the NZ serious injury indicators, miss a material number of serious injury cases of interest? Methods: Empirical methods were used to investigate an alternative definition of serious non-fatal injury. The alternative definition involved relaxing the criteria for PDx to be within the ICD injury chapter, provided there exists an injury diagnosis on the hospital discharge record, and the severity of the injuries recorded on the record exceed a pre-existing agreed threshold. Results, including case scenarios, were presented to a stakeholder group, where agreement on the most appropriate case definition was sought. Results: Relaxing the requirement for the PDx to be an injury resulted in 7% more serious non-fatal injury cases. The largest percentage increase in cases was found for self-harm, which showed a 17% increase. Conclusion: The current NZ case definition potentially misses a material number of serious non-fatal injury cases of interest to the stakeholder community. There is evidence, and agreement with stakeholders, to support the adoption of the more inclusive case definition.